2016
DOI: 10.1186/s40709-016-0053-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of Aeluropus littoralis reference genes for Quantitative Real-Time PCR Normalization

Abstract: BackgroundThe use of stably expressed genes as normalizers has crucial role in accurate and reliable expression analysis estimated by quantitative real-time polymerase chain reaction (qPCR). Recent studies have shown that, the expression levels of common housekeeping genes are varying in different tissues and experimental conditions. The genomic DNA contamination in RNA samples is another important factor that also influence the interpretation of the data obtained from qPCR. It is estimated that the gDNA conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…However, gaining optimal benefits from these advantages requires a clear understanding of the setup of the parameters used for the qPCR experiment. To receive a reliable result in qPCR gene expression analysis, it is necessary to avoid the nonspecific amplification that arises from primer-dimer or gDNA contamination in the RNA sample 3 15 . It is expected that the RNA transcript levels will be overestimated under gDNA contamination 8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, gaining optimal benefits from these advantages requires a clear understanding of the setup of the parameters used for the qPCR experiment. To receive a reliable result in qPCR gene expression analysis, it is necessary to avoid the nonspecific amplification that arises from primer-dimer or gDNA contamination in the RNA sample 3 15 . It is expected that the RNA transcript levels will be overestimated under gDNA contamination 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Since gDNA contamination is not distributed uniformly between different RNA samples, and the reaction sensitivity to gDNA is significantly affected by the genes analyzed, NRT controls are required for each sample/assay pair 7 15 . This will substantially add cost and labor when handling many samples simultaneously 3 9 . Other alternative methods documented in the literature include the use of intron specific primers for the detection of gDNA, or designing primers that either flank an intron or span an exon-exon junction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers (Yael and Ran 2010, Morgante et al 2011, Reddy et al 2013 have reported different patterns of reference genes at different developmental stages, or various experimental conditions in peanut. Differential stability of reference genes in different tissues has also been reported in other plants (Lin et al 2013, Imai et al 2014, Hashemi et al 2016. Some reference genes, like ADH3 and TUA5, have previously been highlighted as the most stable genes in peanut, but they are not suitable to all experimental sets.…”
Section: Discussionmentioning
confidence: 93%